Bmi-1 regulates stem cell-like properties of gastric cancer cells via modulating miRNAs. Issue 1 (December 2016) - Wang, Xiaofeng; Wang, Chang; Zhang, Xiaowei; Hua, Ruixi; Gan, Lu; Huang, Mingzhu; Zhao, Liqin; Ni, Sujie; Guo, Weijian
Abstract Background B cell-specific Moloney murine leukemia virus integration site 1 (Bmi-1) plays an important role in regulating stemness in some kinds of cancer. However, the mechanisms remain unclear. This study was to investigate whether and how Bmi-1 regulates stemness of gastric cancer. Methods We firstly explored the role of Bmi-1 in regulating stem cell-like features in gastric cancer. Secondly, we screened out its downstream miRNAs and clarified whether these miRNAs are involved in the regulation of stemness. Finally, we investigated the mechanisms how Bmi-1 regulates miRNAs. Results Bmi-1 positively regulates stem cell-like properties of gastric cancer and upregulates miR-21 and miR-34a. There was a positive correlation between Bmi-1 and miR-21 expression in gastric cancer tissues. MiR-21 mediated the function of Bmi-1 in regulating stem cell-like properties, while miR-34a negatively regulates stem cell-like characteristics via downregulating Bmi-1. Bmi-1 binds to PTEN promoter and directly inhibits PTEN and thereafter activates AKT. Bmi-1 also regulates p53 and PTEN via miR-21. Bmi-1 activated NF-kB via AKT and enhanced the binding of NF-kB to the promoter of miR-21 and miR-34a and increased their expression. Conclusions Bmi-1 positively regulates stem cell-like properties via upregulating miR-21, and miR-34a negatively regulates stem cell-like characteristics by negative feedback regulation of Bmi-1 in gastric cancer. Bmi-1 upregulates miR-21 and miR-34a by activating AKT-NF-kB pathway.